Peran Kepuasan Karier Pada Upaya Peningkatan Pencapaian Sasaran Kerja Pegawai Pada Sekretariat Daerah Kabupaten Batang - Nova Fatmawatiningtyas; Endah Winarti HS; Siti Hidayah (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
The purpose of this research is to analyze the effect of performance benefits and interpersonal communication on employee performance with career satisfaction as a mediating variable. The population in this study were all employees of the Regional Secretariat of Batang Regency, totaling 114 employees. The number of samples taken in this study were all members of the population using the census method. The data processed after distributing the questionnaires were 101 bundles. Methods of data analysis using regression analysis and data processing using SPSS. The results of hypothesis testing show that performance allowances have a positive and significant effect on career satisfaction, so it can be interpreted that the better the performance allowances, the higher career satisfaction. Interpersonal communication has a positive and significant effect on career satisfaction, so it can be interpreted that the smoother the interpersonal communication, the higher the career satisfaction. Career satisfaction has a positive and significant effect on employee performance, so it can be interpreted that the higher career satisfaction, the better employee performance. Performance allowances have a positive and significant effect on employee performance, so it can be interpreted that the better the performance allowance, the higher the employee performance. Interpersonal communication has a positive and significant effect on employee performance so that it can be interpreted that the smoother the interpersonal communication is carried out, the better the employee performance. The results of the analysis of mediating variables using the Sobel test found that career satisfaction can mediate the effect of performance allowances on employee performance. This proves that career satisfaction is a mediating variable from the effect of performance allowances on employee performance. Career satisfaction can mediate the effect of interpersonal communication on employee performance. This proves that career satisfaction is a mediating variable from the effect of interpersonal communication on employee performance.